Micro-PET Imaging of αβ-Integrin Expression with F-Labeled Dimeric RGD Peptide - Xiaoyuan Chen; Michel Tohme; Ryan Park; Yingping Hou; James R. Bading; Peter S. Conti (Molecular Imaging)
The α v integrins, which act as cell adhesion molecules, are closely involved with tumor invasion and angiogenesis. In particular, α v β 3 integrin, which is specifically expressed on proliferating endothelial cells and tumor cells, is a logical target for development of a radiotracer method to assess angiogenesis and anti-angiogenic therapy. In this study, a dimeric cyclic RGD peptide E[c(RGDyK)] 2 was labeled with 18 F ( t 1 /2 = 109.7 min) by using a prosthetic 4-[ 18 F]fluorobenzoyl moiety to the amino group of the glutamate. The resulting [ 18 F]FB-E[c(RGDyK)] 2 , with high specific activity (200–250 GBq/μmol at the end of synthesis), was administered to subcutaneous U87MG glioblastoma xenograft models for micro-PET and autoradiographic imaging as well as direct tissue sampling to assess tumor targeting efficacy and in vivo kinetics of this PET tracer. The dimeric RGD peptide demonstrated significantly higher tumor uptake and prolonged tumor retention in comparison with a monomeric RGD peptide analog [ 18 F]FB-c(RGDyK). The dimeric RGD peptide had predominant renal excretion, whereas the monomeric analog was excreted primarily through the biliary route. Micro-PET imaging 1 hr after injection of the dimeric RGD peptide exhibited tumor to contralateral background ratio of 9.5 ± 0.8. The synergistic effect of polyvalency and improved pharmacokinetics may be responsible for the superior imaging characteristics of [ 18 F]FB-E[c(RGDyK)] 2 .